(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Coronaviruses are large group of enveloped viruses with unsegmented, single-stranded, positive-sense RNA as genetic material. These are collection related RNA viruses that cause diseases of economically important vertebrate viz. mammals and birds. In humans, these viruses cause respiratory tract infections that can range from asymptomatic to life threatening. The asymptomatic disease include very similar to some cases of the common cold, while other deadly varieties can cause SARS, MERS, and COVID-19. The SARS-CoV (severe acute respiratory syndrome coronavirus) and MERS-CoV (Middle East respiratory syndrome coronavirus) are zoonotic origin and extremely pathogenic coronaviruses that can cause localized and worldwide outbreak. The novel Coronaviruses, COVID-19 posses a unique morphology. The outer surface of the virus bearing surface spike and reveled like crown hence being named corona virus. The mode of replication of the virus is very unique as it replicate through the generation of nested set of viral mRNA. The HCoV (Human coronavirus) cause respiratory complication with asymptomatic to life threatening outcomes. From the past 15 years we have witnessed appearance of two zoonotic, extremely pathogenic human corona viruses the: SARS-CoV and MERS-CoV.